Agricultural productivity and employment gains in watershed projects of Madhya Pradesh - Gautam, Manu (New Delhi : Indian Council of Social Science Research, 2013)
Watershed management is one of the most required aspects of Indian Agriculture. In today's scenario where severe shortage of irrigation water is posing a serious question on the sustainability of Indian agriculture; the management of watershed has shown a potential of reviving the sagging hopes. Watershed management involves a whole range of activities which not only addresses the issues of water shortage but also manages various other issues of economic development. Employment generation is one of the direct benefits of watershed development where villagers get employment in their villages. It is one of the effective ways to reduce migration in search of employment to other places.
Indian Council of Social Science Research
English
Keywords: Agricultural productivity -- Madhya Pradesh; Watershed management -- Madhya Pradesh